Pelatihan Model Pembelajaran Berbasis Tutor Balibolae Guna Percepatan Pemberantasan Buta Aksara - Salmiati Salmiati; Ahmad Yusuf; Rosmawati Rosmawati (STKIP Andi Matappa, 2020)
Abstract. The aim of the community service is to provide training in Balibolae tutor-based learning models to accelerate illiteracy eradication. The methods used are 1) coordination with the village head of Panaikang, 2) Forming learning citizen groups, 3) Recruiting BalibolaE tutors from neighboring learning residents, 4) Tutor training balibolaE, 5) Delivery of balibolaE tutor training materials, 6) Providing balibolaE tutor training, 7) BalibolaE tutor training closing activities. The results of the activity: (a) The implementation of BalibolaE tutor-based learning model training has been able to improve the performance of the reading, writing and counting skills of learning citizens in Panaikang Village, Pangkep Regency (b) BalibolaE tutor-based accelerated learning model objectives, objectives, activity systematics and time allocation, place and character of tutor participants, tutor requirements, tutor learning approaches, tutor teaching methods, teaching methods and learning materials.